2021
DOI: 10.1016/j.msec.2020.111735
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 bioactive implant surfaces doped with specific amount of Sr modulate mineralization

Abstract: One of the main problems that remain in the implant industry is poor osseointegration due to bioinertness of implants. In order to promote bioactivity, calcium (Ca), phosphorus (P) and strontium (Sr) were incorporated into a TiO 2 porous layer produced by micro-arc oxidation. Ca and P as bioactive elements are already well reported in the literature, however, the knowledge of the effect of Sr is still limited. In the present work, the effect of various amounts of Sr was evaluated and the morphology, chemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 91 publications
2
20
0
Order By: Relevance
“…Besides, it has to be mentioned that Ca and Sr may be other factors that promote cell proliferation, since Ca and Sr are important components during bone formation. Extensive studies have demonstrated that the introduction of Ca and Sr in the coatings greatly favors excellent cell proliferation and ALP activity of osteoblasts [34,35]. In this study, the presence of Ca and Sr possibly helped to promote cell proliferation and ALP activity.…”
Section: Cell Activity and Alp Activitymentioning
confidence: 64%
“…Besides, it has to be mentioned that Ca and Sr may be other factors that promote cell proliferation, since Ca and Sr are important components during bone formation. Extensive studies have demonstrated that the introduction of Ca and Sr in the coatings greatly favors excellent cell proliferation and ALP activity of osteoblasts [34,35]. In this study, the presence of Ca and Sr possibly helped to promote cell proliferation and ALP activity.…”
Section: Cell Activity and Alp Activitymentioning
confidence: 64%
“…The morphology of coatings after PEO features a rough surface with numerous highly interconnected micropores, which are distributed homogeneously and ranging at micro levels, 164 and it is often described as "craterlike" and "volcano-like" in the literature. 23,101 Furthermore, small grains in the nanoscale range are revealed in high-magnification analysis. 36,43,113,117,130,136,144,163,173 Importantly, the incorporation of inorganic elements rarely affects the morphology including pore size and pore distribution (Fig.…”
Section: Peo Coating Characteristics: Physicochemical Properties and ...mentioning
confidence: 99%
“…2). 23,43,101,104,109,114,121,152 This unique morphology of PEO coatings is believed to ameliorate the process of osseointegration since the porous structure can optimize the implantbone interface from both macro (strong mechanical interlocking: the ingrowth of bone) and micro (suitable micro-environment for cells: large and interconnected growing space) dimensions. Interestingly, a study conducted by Li et al has represented a novel "cortex-like" micro/nano dual-scale structured TiO 2 coating manufactured by micro-arc oxidation (MAO) with tetraborate electrolytes (Fig.…”
Section: Peo Coating Characteristics: Physicochemical Properties and ...mentioning
confidence: 99%
“…Strontium ion (Sr 2+ ) is one of the rare-earth metals widely used in manufacturing, such as ferrite magnets, ceramics, glass, and fireworks. 27,31 The concentration of Sr 2+ in natural seawater is about 7 mg•L −1 . The recycling of Sr 2+ from seawater is simpler, less costly, and more environmentally friendly than the traditional extraction method of mining ores on land.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Seawater is rich in mineral resources, including dissolved metals in the form of ions. Strontium ion (Sr 2+ ) is one of the rare-earth metals widely used in manufacturing, such as ferrite magnets, ceramics, glass, and fireworks. , The concentration of Sr 2+ in natural seawater is about 7 mg·L –1 . The recycling of Sr 2+ from seawater is simpler, less costly, and more environmentally friendly than the traditional extraction method of mining ores on land. At present, the commonly used adsorbents for extracting Sr 2+ from seawater are mainly alginate microbeads. The disadvantage of these materials is that the alginate is prone to over-swelling by absorbing water and transforming into hydrogel .…”
Section: Introductionmentioning
confidence: 99%